2013
DOI: 10.1021/jp4046269
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Nature and Location of Silver in Ag-Exchanged Mordenite Catalysts. Characterization by Spectroscopic Techniques

Abstract: Catalysts based on Na-mordenite (symbolized as 'M') exchanged with 5, 10 and 15 wt. % of Ag were characterized by XPS, EXAFS, XANES and UV-Vis DRS spectroscopic techniques in order to investigate the effect of different treatments on the chemical state and surface concentration of silver species. The Ag x M catalysts were analyzed in oxidizing (O 2 ) or reducing (H 2 /Ar) atmospheres and also after being used in the selective catalytic reduction of NOx or in successive cycles of toluene adsorption/desorption.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 56 publications
8
42
0
3
Order By: Relevance
“…[27] To assess the oxidation state(s) of extra-framework Lewis acids ites in Ag-ZSM-5, we used X-ray photoelectron spectroscopy (XPS)t oc haracterize as-prepared and calcined Ag 25 -ZSM-5. XPS spectra ( Figure 1B)r eveal two bands at 375.3 and 369.3 eV separated by 6eV, which are assigned to Ag 3d 3/2 andA g3d 5/2 ,r espectively.T hese two characteristic bands are consistent with reported values of Ag-ZSM-5 and AgNO 3 , [28] indicating that both as-prepared and calcined Ag 25 -ZSM-5 are predominantly comprised of Ag + species. Interestingly,X PS surfacea nalysis of as-prepared Ag 25 -ZSM-5 indicates an Ag/Al ratio that is nearly two-fold higher than the value measured by EDX (0.24 AE 0.07).…”
Section: Resultssupporting
confidence: 88%
“…[27] To assess the oxidation state(s) of extra-framework Lewis acids ites in Ag-ZSM-5, we used X-ray photoelectron spectroscopy (XPS)t oc haracterize as-prepared and calcined Ag 25 -ZSM-5. XPS spectra ( Figure 1B)r eveal two bands at 375.3 and 369.3 eV separated by 6eV, which are assigned to Ag 3d 3/2 andA g3d 5/2 ,r espectively.T hese two characteristic bands are consistent with reported values of Ag-ZSM-5 and AgNO 3 , [28] indicating that both as-prepared and calcined Ag 25 -ZSM-5 are predominantly comprised of Ag + species. Interestingly,X PS surfacea nalysis of as-prepared Ag 25 -ZSM-5 indicates an Ag/Al ratio that is nearly two-fold higher than the value measured by EDX (0.24 AE 0.07).…”
Section: Resultssupporting
confidence: 88%
“…The curves indicate that there is no further increase in iodine loading capacity beyond the reduction conditions of 673 K and 24 h, which indicated that, at these optimal conditions, the AgZ was fully reduced. Therefore, this set of conditions is the optimal reduction conditions for the AgZ used in the current study and is supported by similar studies in the literature …”
Section: Resultssupporting
confidence: 78%
“…In theory, if all of the 12.0 wt % (1.10 mmol Ag/g) silver was reacted with iodine through the reaction 2Ag + I 2 → 2AgI to form AgI, the theoretical maximum iodine adsorption capacity of the Ag 0 Z would be 14.1 wt % (1.10 mmol I/g). It is noted that before reduction Ag is largely in the crystalline framework of AgZ as Agx+ (AlO 4 ) −1 x (SiO 2 ) 5 x and that after reduction in hydrogen at 673 K for 24 h or more severe conditions, Ag was shown to be reduced to Ag 0 by XRD and XAFS analysis …”
Section: Methodsmentioning
confidence: 99%
“…[163][164][165][166][167][168] In the particular case of the capture of iodine species, the adsorption properties and cation exchange capacities of zeolites make them interesting and remarkable candidates for this application. In the literature, several zeolites of different structural types have been studied for the capture of iodine species, such as mordenite (MOR structural type), 29,34,74,76,77,79,80,[169][170][171][172][173][174][175][176][177][178] NaX and NaY zeolites (FAU type), 5,60,75,77,78,88,132,179 ZSM-5 (MFI type), 74,77 ferrierite (FER type) and zeolite beta (*BEA type) 74,77 (ESI, Table 3 †).…”
Section: Ag-exchanged Zeolitesmentioning
confidence: 99%